Mediating Role of Social Media in the Memorability of Street Sculpture Art: Jogja Street Sculpture Project 2017 as Case Study - Wegig Murwonugroho, (Wacana Seni Journal of Arts Discourse, 2019)
Street sculpture art is sculpture that is deliberately presented in public spaces. The Jogja Street Sculpture Art 2017 event chose the Kotabaru area as a public space in which to display statues. There were various forms of public responses to the statues. The physical environment where a statue is placed is the primary field and the awareness of sculptures has become increasingly prevalent because pictures of sculptures are increasingly frequently uploaded on social media platforms. Social media has become an important field in which the public can respond to statues without seeing them physically. A statue, whether it inspires discourse or not, can become dominant in the field of social media. Eventually, a gap forms regarding whether a statue is in discourse with other statues. This research study attempts to identify how sculptures have occupied the physical world and social media has helped to determine the sculptures' level of memorability. This study uses the critical discourse analysis (CDA) research method. The results of the analysis show that memorability is influenced by the irregularities of a statue's visual elements, the relationship between the physical environment and the narrated, hyperrealistic historical background and the statue's level of memorability, the last of which is affected by the factor of entertainment. The study concludes that the visual achievement of street sculpture art is no longer seen in terms of the power of the aesthetic elements of a sculpture's visual structure but is influenced and publicised by the power of social media. This means that the content generators of social media have power over the visibility and enjoyment of street sculpture art. Hence, public power has been used as a foundation for social media accounts, regardless of whether the statue itself is memorable.